Can a unilateral carbon tax reduce emissions elsewhere? - Joshua Elliott; Don Fullerton (Center for Economic Studies and ifo Institute (CESifo), 2013)
One country that tries to reduce greenhouse gas emissions may fear that other countries get a competitive advantage and increase emissions (leakage). Estimates from computable general equilibrium (CGE) models such as Elliott et al (2010a,b) indicate that 15% to 25% of abatement might be offset by leakage. Yet the Fullerton et al (2012) analytical general equilibrium model shows an offsetting term with negative leakage. To derive analytical expressions, their model is quite simple, with only one good from each country or sector, a fixed stock of capital, competitive markets, and many identical consumers that purchase both goods. Their model is not intended to be realistic, but only to demonstrate the potential for negative leakage. Most CGE models do not allow for negative leakage. In this paper, we use a full CGE model with many countries and many goods to measure effects in a way that allows for negative leakage. We vary elasticities of substitution and confirm the analytical model's prediction that negative leakage depends on the ability of consumers to substitute into the untaxed good and the ability of firms to substitute from carbon emissions into labor or capital.
Keywords: Q48; Q54; Q58; 330; carbon policy; trade; pollution haven